Penerapan Model Pembelajaran Laps-Heuristik di Sekolah Dasar/Madrasah Ibtidaiyah - Suparlan Suparlan (Pendidikan Islam Anak Usia Dini STIT Palapa Nusantara, 2022)
Learning is a communication process that includes two directions, namely teaching carried out by the teacher as an educator and learning carried out by students as students. While Corey provides a definition that learning is a process in which a person's environment is deliberately managed to enable him to participate in certain behaviors under special conditions and produce certain responses. Laps-Heuristic learning is a way of learning to think systematically by confronting students with problems or problems they face. Another definition of Laps-Heuristic learning is a way of teaching that is done by training students (students) to face various problems to be solved individually or together.